TINJAUAN YURIDIS PUTUSAN PERKARA NOMOR 53/PDT.G/2015/PN.Pbr TERHADAP PERCEKCOKAN SEBAGAI ALASAN PERCERAIAN DI PENGADILAN NEGERI KELAS 1 A PEKANBARU (Studi Putusan Nomor 53/Pdt.G/2015/PN.Pbr) - Ananda Jelita Putri; Mardalena Hanifah; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Marriage is a spiritual and physical bond between a man and a woman who has grown up under the provisions of the applicable legislation and is eternal and immutable toward domestic life happy and prosperous. The breakdown of marriage is the end of a marriage that has been fostered by the couple, which is caused by several things, such as death, divorce, and the court's decision. In contrast to what happened in pair Deddy Sosandy Hutapea and Evi romian Boru Sitorus, the reason for divorce is a divorce decision made by the District Court 1 Class A Pekanbaru with case number, No. 53 / Pdt.G / 2015 / PN.Pbr. the chronology is' Deddy Sosandy Hutapea divorce his wife Evi romian Boru Sitorus arguing that Evi romian Boru Sitorus a defendant can not take care of a child with a good result the child several times falls well short of the bed and in the bathroom as a reason for divorce. Based on the above, the writer wanted to know How consideration of the judge in the case decided fray as the reason of divorce (the study of decision No. 53 / Pdt.G / 2015 / PN.Pbr, and whether the consideration of judges in decision No. 53 / Pdt.G / 2015 / PN.Pbr, that it meets the principle of legal certainty.This type of research if viewed from the angle of its kind, this research can be classified to the normative research. Normative research is legal research library that includes the study of the principles of law, the source of the data used are primary data and secondary data, this research technique to the study of literature and interviews.From the research and analysis of the author based on the principle of legal certainty in mind first, the reasons for the decision in case No. 53 / Pdt.G / 2015 / PN.Pbr not in accordance with the legal basis and the existing arrangements is based on Article 39 of the Marriage Law No. 1 1974. On the basis of the proposed plaintiff judges should not be in favor of the plaintiff.Keywords: Decision, Reason Disputes, Divorce.